MFGE8/Integrin β3 Pathway Alleviates Apoptosis and Inflammation in Early Brain Injury after Subarachnoid Hemorrhage in Rats - Liu, Fei (Exp Neurol, 2015)
BACKGROUND: Milk fat globule-epidermal growth factor-factor 8(MFGE8)/Integrin β3 pathway was reported to be involved in reducing oxidative stress and early brain injury after Subarachnoid Hemorrhage (SAH). In the present study, the potential effects of MFGE8 and its receptor Integrin β3 in the inhibition of apoptosis and neuroinflammation in early brain injury after SAH were investigated. METHODS: Ninety-five (95) male Sprague-Dawley rats were used. The SAH model was induced by endovascular perforation. Recombinant human MFGE8 (rhMFGE8), MFGE8 small interfering RNA (siRNA) and Integrin β3 siRNA were injected intracerebroventricularly. SAH grade, neurologic scores, Western blots and immunofluorescence were employed to study the mechanisms of MFGE8 and its receptor Integrin β3, as well as neurological outcome. RESULTS: SAH induced significant neuronal apoptosis and inflammation and exhibited neurological dysfunction in rats. Knockdown endogenous MFGE8 with siRNA significantly increased the protein levels of cleaved caspase 3 and IL-1β, accompanied with more neurological deficits. rhMFGE8 significantly reduced neural cell death in cortex, decreased cleaved caspase 3 and IL-1β expressions, and improved neurological functions 24 hours after SAH. The anti-apoptosis and anti-inflammation effects of rhMFGE8 were abolished by integrin-β3 siRNA. CONCLUSION: MFGE8 could alleviate neurologic damage in early brain injury after SAH via anti-inflammation and anti-apoptosis effects. MFGE8 may serve as a promising therapeutic target for future management of SAH patients.